Determinasi Teknologi Komunikasi Pedesaan dan Perkotaan di Wilayah Mojokerto - Ratnaningrum Zusiyana Dewi; Fatihatul Lailiyah (Jurnal Nomosleca, 2020)
Determination of technology is a major change that occurs in communities both in rural and urban areas. This is caused by the development of communication technology that moves very fast and dynamic. The changes that occur lead people to continuously adapt to changing patterns of daily life. This change causes a shift in values, how to interact, how to communicate, manners, manners, and other everyday cultures. This study aims to determine the determination of rural and urban communication technology in the district and city of Mojokerto. The results showed that the rural / urban communication system that occurred in the region. There are many kinds of communication that occur in each Kelurahan, the differences are very prominent in each region. These differences do not become a barrier for loyal people in communicating. Even though it is located in the city, the local population still upholds the culture and noble values of the local culture, such as gamelan, rice grass, death fees, community gatherings, patrols, recitation, and socialization about the dangers of dengue fever mosquitoes. The information media in this kelurahan comes from newspapers, magazines and bulletins, however the residents in this kelurahan seem to have less interest in buying the printed media, therefore the subscribers are approximately 72 residents, maybe this is due to the increasingly modern era and the population. who are very knowledgeable about technology.Keywords: Determinism of Communication, Rural and Urban Communication Systems.